First results from the LIFE project: discovery of two magnetic hot evolved stars. Issue 2 (20th December 2017) - Martin, A J; Neiner, C; Oksala, M E; Wade, G A; Keszthelyi, Z; Fossati, L; Marcolino, W; Mathis, S; Georgy, C
Abstract: We present the initial results of the Large Impact of magnetic Fields on the Evolution of hot stars (LIFE) project. The focus of this project is the search for magnetic fields in evolved OBA giants and supergiants with visual magnitudes between 4 and 8, with the aim to investigate how the magnetic fields observed in upper main-sequence (MS) stars evolve from the MS until the late post-MS stages. In this paper, we present spectropolarimetric observations of 15 stars observed using the ESPaDOnS instrument of the Canada–France–Hawaii Telescope. For each star, we have determined the fundamental parameters and have used stellar evolution models to calculate their mass, age, and radius. Using the least-squared deconvolution technique, we have produced averaged line profiles for each star. From these profiles, we have measured the longitudinal magnetic field strength and have calculated the detection probability. We report the detection of magnetic fields in two stars of our sample: a weak field of B l = 1.0 ± 0.2 G is detected in the post-MS A5 star 19 Aur and a stronger field of B l = −230 ± 10 G is detected in the MS/post-MS B8/9 star HR 3042.